Students' Psychological Problems in Speaking at Nursing Science - Rani Autila (Lembaga Penelitian dan Pendidikan Mandala, 2025)
EFL students do not only have linguistic problems but also psychological problems when learning English. The present study aims to describe psychological problems in speaking. This study was conducted under descriptive design. Participants in this study were 33 fourth-semester students of Nursing Science at Sekolah Tinggi Ilmu Kesehatan Indonesia (STIKESI). The instrument used in this study is an online questionnaire. The findings indicate that although anxiety, lack of confidence, and fear of making mistakes are significant problems, respondents showed a generally neutral attitude toward these problems. However, the presence of these psychological barriers, coupled with shyness and lack of motivation, suggests that targeted interventions are needed to improve English-speaking performance among respondents.